Competition anxiety and mental toughness in badminton student-athletes’ performance - Muhammad Labib Siena Ar Rasyid; Oce Wiriawan; Afif Rusdiawan; Yanuar Alfan Triardhana; Naila Khanina (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Psychological factors such as anxiety and mental toughness play an important role in competitive sports, particularly during high-pressure selection processes. Studies on psychological predictors in internal sports selection remain limited. This study aims to examine the relationship between competition anxiety, mental toughness, and competition performance. Performance was assessed through two measures: subjective performance (self-perceived performance) and match outcomes in the internal selection process. This study used a correlational quantitative design. A total sampling technique was applied, in which all male student-athletes registered in the internal selection were invited to participate, resulting in 23 male badminton student-athletes from a university in Surabaya, Indonesia, participating in the study. The research instruments used were the Sport Anxiety Scale-2 (SAS-2), the Mental Toughness Questionnaire-10 (MTQ-10), and subjective performance and match outcome measures. Data were analyzed using Pearson correlation and Spearman's rank correlation tests. Pearson correlation results showed a relationship between competition anxiety and subjective performance (r = -0.708, p < 0.05) and between mental toughness and subjective performance (r = 0.606, p < 0.05). Spearman's rank correlation results showed a relationship between competition anxiety and match outcomes (r = -0.451, p < 0.05), while mental toughness showed no significant relationship with match outcomes (r = 0.249, p > 0.05). These findings indicate that competition anxiety and mental toughness are significantly related to subjective performance. However, when performance is evaluated based on match outcomes, only competition anxiety shows a significant relationship, indicating that competition anxiety has a greater influence on match outcomes in internal selection contexts.